Study of Humanistic Education: Concerns, Implications, and Applications - Mark Treve (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Humanistic is an approach recommended by the ideas of intellectuals, and Scholars like Erickson, Roger, and Maslow began to infuse the field of second language teaching and learning towards the end of 1970. According to Lei (2007), the humanistic approach emphasizes the importance of the inner world of the learner and places the individual's thoughts, emotions, and feelings at the limelight of all human development. As a result of this new shift of focus, language education, and pedagogy changed away from the previous behavioristic and mentality approaches, and consequently, a new kind of education known as humanistic education emerged. Besides, significant changes occurred in all aspects of language education; that is, the traditional roles of teachers and learners redefined, and learner-centered classrooms replaced the previously authoritarian teaching practices. This paper is two-fold. Firstly, it is going to take a detailed look at the main principles and features of humanistic education, and secondly, it aims at discussing the implications and applications of humanistic education. Lastly, it tries to clarify the new roles and responsibilities considered for language teachers to be able to engage the students in the learning process fully.